Serotonin signaling modulates the effects of familial risk for depression on cortical thickness. (28th February 2016) - Bansal, Ravi; Peterson, Bradley S.; Gingrich, Jay; Hao, Xuejun; Odgerel, Zagaa; Warner, Virginia; Wickramaratne, Priya J.; Talati, Ardesheer; Ansorge, Mark; Brown, Alan S.; Sourander, Andre; Weissman, Myrna M.
Abstract: Depression is a highly familial and a heritable illness that is more prevalent in the biological offspring of the depressed individuals than in the general population. In a 3-generation, 30-year, longitudinal study of individuals at either a high(HR) or a low(LR) familial risk for depression, we previously showed cortical thinning in the right hemisphere was an endophenotype for the familial risk. In this study, we assessed whether the effects of familial risk were modulated by the serotonin-transporter-linked polymorphic region (5-HTTLPR). We measured cortical thickness using MRI of the brain and associated it with 5-HTTLPR polymorphism in 76 HR and 53 LR individuals. We studied the effects of genotype and gene-by-risk interaction on cortical thickness while controlling for the confounding effects of age and gender, and for the familial relatedness by applying a variance component model with random effects for genotype. The results showed significant effects of gene-by-risk interaction on thickness: The "s" allele was associated with thinner cortex in the LR individuals whereas with thicker cortex in the HR individuals. The opposing gene effects across the two risk groups were likely due to either epistatic effects and/or differing modulation of the neural plasticity by the altered 5-HT signaling in utero . Highlights: Cortical thinning in right later hemisphere is a risk endophenotype for depression. We hypothesized that 5-HTTLPR polymorphism will moderate risk effects on the cortex. Our results showed significant effects of risk-by-gene interaction on the cortex. Interaction effects likely are due to blunted plasticity conferred by the "s" allele.